Disrupted Regional Homogeneity in Major Depressive Disorder With Gastrointestinal Symptoms at Rest - Yan, Meiqi; Chen, Jindong; Liu, Feng; Li, Huabing; Huang, Renzhi; Tang, Yanqing; Zhao, Jingping; Guo, Wenbin (Frontiers in Psychiatry, 2021)
Background: Gastrointestinal (GI) symptoms are prominent in patients with major depressive disorder (MDD). Previous studies have reported brain structural and functional changes in both MDD and digestive system diseases but it remains unclear whether MDD patients with GI symptoms have brain imaging changes. Methods: We recruited 35 MDD patients with GI symptoms, 17 MDD patients without GI symptoms and 28 age-, gender-, and education-matched healthy controls. All participants were scanned by resting-state functional magnetic resonance imaging (fMRI). Imaging data were analyzed with regional homogeneity (ReHo). Results: The GI group showed higher total HRSD-17 scores, anxiety/somatization, weight loss, and sleep disturbance scores compared to the non-GI group. We found increased ReHo in the right inferior parietal gyrus (IPL), bilateral supplementary motor area (SMA), bilateral cerebellum Crus II, left inferior frontal gyrus (IFG), and bilateral superior medial frontal cortex (SMFC) and decreased ReHo in the right posterior cingulate cortex (PCC), bilateral cuneus, and left middle occipital gyrus (MOG) in patients with GI symptoms relative to the HCs. The GI group showed higher ReHo values in the bilateral precuneus than the non-GI group. Conclusion: MDD patients with GI symptoms showed a greater severity of symptoms than MDD patients without GI symptoms, particularly in terms of anxiety/somatization, weight loss, and sleep disturbances. Increased activity in the default-mode network might be associated with GI symptoms in MDD patients.